Exploring the barriers in implementation of qlassic in Malaysian construction industry from the perspective of contractors - Zahrizan, Zakaria; Mohammad Affendy, Omardin; Khalimi Johan, Abd Hamid (Institute of Physics, 2023)
Construction industry is one of the largest contributors to the economy in Malaysia. Many studies have showed the significant of the construction industry contribution but the issues of properties buyers especially still apprehensive in the industry. National House Buyers Association (HBA) has recorded thousands of complaints from buyers who were not satisfied with the condition of their new properties or the way defects were rectified. The main objectives of QLASSIC is to increase the quality of building but after more a decade the implementation of QLASSIC still lagging behind and there are still many developers and contractors are reluctant to use QLASSIC approach in their projects. Therefore, the main goal of this study is to explore the factor hindering the implementation of QLASSIC in Malaysia especially from the contractors' perspective. Questionnaires were used as research instrument for collecting data information, then the data were analysed by using Relative Importance Index (RII). From the analysis, it is found that the main factors that could hinder the implementing of QLASSIC are; lack of coercive and mimetic pressures, lack of capabilities of staff in perform QLASSIC assessment practice due to minor size and type of organisation influence in adopting QLASSIC, higher cost to undergo training to operate QLASSIC's tools and minimal benefits gained when adopting QLASSIC. In conclusion, it's important to tackle the actual factors hindering the implementation of QLASSIC in Malaysian construction industry. Concurrently, every parties in the construction industry should play their roles in promoting the use of QLASSIC in their construction project. Besides that, the government has to make a new strategy in promoting the use of QLASSIC by providing incentive such as tax rebate if the contractors used QLASSIC assessor to access their projects.